SURDOS, TECNOLOGIAS ASSISTIVAS E ESTUDOS DE AULA: UMA PERSPECTIVA ETNOMATEMÁTICA EM FOCO - Antunes, Maria de Fátima Nunes (2023)
The objective of this thesis is to analyze the pedagogical contributions of the Classroom Studies methodology in its intersections with the field of ethnomathematics and the use of GeoGebra as an Assistive Technology for deaf students. The participants in the first stage of the research were the regular teachers of 3rd and 4th-grade classes in the early years, the sign language interpreter, and the Multifunctional Resource Room of a state school in Guarantã do Norte/MT. They continued their studies in the second stage at a public school in Sinop/MT where the Multifunctional Resource Room teacher and two deaf students (also teachers), one of whom was invited, were involved. In all stages, the group developed, redesigned, and evaluated spatial geometry activities using GeoGebra as an Assistive Technology (AT). The chosen classes to develop and reapply the tasks were the 4th grade in Guarantã do Norte and the 3rd grade in Sinop/MT. Finally, the group returned to the first investigated school to work with a 5th-grade class, which, like the previous ones, had a deaf student. For data generation, field diaries, recordings, participant observation, printed tasks, and subsequent transcription of these data involving the participants were used. The results were guided by descriptive research with the support of Nvivo Software, and out of four, three were project maps and articulation levels according to Blanco-Álvarez (2022). The first one, Inclusion and Curriculum, indicated the potential of the Classroom Studies methodology for enhancing teaching processes in the early years of elementary education, especially considering the right of a deaf teacher to lead regular classes, provided they had specific training in the area and the right to a sign language interpreter. Communication between deaf teachers and students was more consistent in regular classrooms as they had their own visual communication and used the same language in the context of teaching and learning. The second one, Deaf Student, showed that hearing students also learned by interacting with the deaf student, as he shared his learnings through visual means. In the third, in the research developments, the idea emerged that GeoGebra is an Assistive Technology for the deaf and enhances learning for hearing students. In the fourth, Compliance with the Amplifying/Articulating Criteria of Blanco-Álvarez (2022), there is evidence that, in actions developed in inclusive classrooms, deaf individuals used elements of their culture when thinking, teaching, discussing, and responding to spatial geometry tasks. Additionally, an educational product, entitled The movement of class studies with a focus on spatial geometry aimed at deaf culture: propositions of a didactic sequence, was created in the form of a video in Brazilian Sign Language (LIBRAS) and Portuguese, as well as Colombian Sign Language (LSC) and Spanish, addressing spatial geometry through the use of GeoGebra as an AT. The purpose of the video production is to contribute to the studies of deaf education, for example, in the continuous training of teachers involved in this inclusion process in Brazil, Colombia, and other countries.